Numerical solution of FIE of the second kind with cauchy kernel - Eshkuvatov, Zainidin K.; Mahiub, Mohammad Abdulkawi; Nik Long, Nik Mohd Asri (American Institute of Physics, 2011)
In this paper, we present numerical method for solving the Fredholm Integral Equation of the second kind with Cauchy kernel. The weighted Chebyshev polynomials of the second kind are used to approximate the unknown function. Inconstant coefficients are approximated by Chebyshev polynomials of the first kind. Special type of regular integrals are computed analytically. Finally, numerical results show the exactness and accuracy of the numerical method presented.